TEACHER AS A PRINCIPLE ELEMENT OF THE “FLIPPED CLASSROOM” TECHNOLOGY - T. A. Borzova (Высшее образование в России)
The article analyzes the experience of the Flipped Classroom technology implementation on the example of “Russian Language and Culture of Speech” discipline. The author has summarized the results of a student survey that prove the effectiveness of a digital educational environment as means of optimizing classroom lectures. The article focuses on technological, scientific, and methodological aspects of teacher’s activity in conditions of changing his/her roles – from “sage on the stage” (lecturer) to “guide on the side” (tutor, instructor); it also defines the competences of higher education teachers that are relevant in the conditions of Flipped Classroom technology implementation. The article shows the important role of a higher education teacher who is at the same time a scientist, a counselor, a manager of electronic educational environment, a tutor, and a curator for a new generation of future specialists in different fields. The professionalism of a higher education teacher has a strong impact on the teaching materials, the effectiveness of methods and forms of individual studies, and classroom interaction.